# Please solve the following equation: 2.5(x-3)+1.7x=10.8(x+1.5)Include a step by step how you solved the problem. Your help is much appreciated!

*print*Print*list*Cite

The answer to this is that x = - 3.59. Here is how you get this.

First, multiply out the stuff that is in the parentheses. In other words, multiply each term in the first parentheses by 2.5 and multiply each term in the second parentheses by 10.8. You will get:

2.5x - 7.5 + 1.7x = 10.8x + 16.2

Add 7.5 to both sides.

2.5x + 1.7x = 10.8x + 23.7

Now add the x terms on the left.

4.2x = 10.8x + 23.7

Now subtract 10.8x from both sides so as to have all the x terms on one side of the equation.

-6.6x = 23.7

Now divide both sides by -6.6

x = - 3.59

2.5(x-3)+ 1.7x = 10.8(x+1.5)

Distribute the numbers in front of the parentheses:

2.5x - 7.5 + 1.7x = 10.8x + 16.2

Move like terms to the same side:

2.5x + 1.7x - 10.8x = 16.2 + 7.5

Combine like terms terms:

-6.6x = 23.7

Divide by -6.6 to get x :

`x= 23.7/-6.6`

x = -3.59

2.5(x-3)+ 1.7x = 10.8(x+1.5)

Distribute the 2.5 and the 10.8:

2.5x - 7.5 + 1.7x = 10.8x + 16.2

Move like terms to the same side:

2.5x + 1.7x - 10.8x = 16.2 + 7.5

Combine the terms:

-6.6x = 23.7

Now divide by -6.6 to get x alone:

x= 23.7/-6.6

x = -3.59

2.5x-2.5(3)+1.7x=10.8x+10.8(1.5)

2.5x-7.5+1.7x=10.8x+16.2

4.2x-7.5=10.8x+16.2

10.8x-4.2x=-7.5-16.2

6.6x=-23.7

x=-23.7:6.6=-3.591

The Given equation is:

2.5(x - 3) + 1.7x = 10.8(x + 1.5)

Solving the equation means finding the value of 'x' in this equation.

This can be done as follows:

Step 1: Open the brackets

2.5x - 2.5*3 + 1.7x = 10.8x + 10.8*1.5

==> 2.5x - 7.5 + 1.7x = 10.8x + 16.2

Step 2: Transfer all terms of equation containing x to left hand side and other terms containing only numbers to tight hand side of equation.

==> 2.5x + 1.7x - 10.8x = 16.2 + 7.5

Please note that when we change the side of any term its sign gets reversed from + to -, and vice versa.

Step 3: Add terms on each side of equation.

==> -6.6x = 23.7

Step 4: Divide both side of equation by 6.6. This done so that the left hand side will become equal to x.

==> x = 23.7/(-6.6) = -3.591